2017
DOI: 10.1007/s10712-017-9408-4
|View full text |Cite
|
Sign up to set email alerts
|

Convective Self-Aggregation in Numerical Simulations: A Review

Abstract: Organized convection in the Tropics occurs across a range of spatial and temporal scales and strongly influences cloud cover and humidity. One mode of organization found is "self-aggregation", in which moist convection spontaneously organizes into one or several isolated clusters despite spatially homogeneous boundary conditions and forcing. Self-aggregation is driven by interactions between clouds, moisture, radiation, surface fluxes, and circulation, and occurs in a wide variety of idealized simulations of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
262
2
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 194 publications
(289 citation statements)
references
References 72 publications
24
262
2
1
Order By: Relevance
“…As mentioned in Wing et al (2017), this kind of exponential growth will lead to much larger scales in a given amount of time when starting from larger initial clustering, as is typically found in nature. In other words, much of the time scale for selfaggregation from homogeneous initial conditions may not be especially relevant to comparisons with nature because these time periods involve spinning up mesoscale activity from extremely small initial length scales (and may also involve gestation periods before aggregation begins at all).…”
Section: Time Scales Of Self-aggregationmentioning
confidence: 80%
See 4 more Smart Citations
“…As mentioned in Wing et al (2017), this kind of exponential growth will lead to much larger scales in a given amount of time when starting from larger initial clustering, as is typically found in nature. In other words, much of the time scale for selfaggregation from homogeneous initial conditions may not be especially relevant to comparisons with nature because these time periods involve spinning up mesoscale activity from extremely small initial length scales (and may also involve gestation periods before aggregation begins at all).…”
Section: Time Scales Of Self-aggregationmentioning
confidence: 80%
“…We focus on those which could be targeted in observations; a more complete review can be found in Wing et al (2017).…”
Section: Observational Perspectives On Processes Important For Idealizedmentioning
confidence: 99%
See 3 more Smart Citations